2019
DOI: 10.1149/2.0871915jes
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally Grown SnO2 Flowers as Efficient Electrode Modifier for Simultaneous Detection of Catechol and Hydroquinone

Abstract: Tin oxide (SnO 2 ) flowers were synthesized by hydrothermal method using SnCl 2 .H 2 O as precursor. The formation/phase purity of the hydrothermally grown SnO 2 flowers was determined by PXRD analysis. The morphological surface structure of SnO 2 flowers was checked by SEM analysis whereas the surface area was examined by BET analysis. Further, SnO 2 flowers were deposited on the neat and clean surface of the glassy carbon electrode using drop casting method. This constructed electrode was employed for simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…In this connection, various conventional methods such as fluorescence, spectrophotometry, chromatography, and colorimetric methods have been used for the detection of H 2 O 2 [ 11 , 12 , 13 , 14 , 15 ]. In the past few years, electrochemical methods have received huge interest because of their low cost, simple fabrication, high sensitivity, selectivity, and stability [ 16 , 17 , 18 , 19 , 20 , 21 ]. Previously, electrochemical methods have been widely used for the detection of hazardous/toxic compounds or biomolecules [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, various conventional methods such as fluorescence, spectrophotometry, chromatography, and colorimetric methods have been used for the detection of H 2 O 2 [ 11 , 12 , 13 , 14 , 15 ]. In the past few years, electrochemical methods have received huge interest because of their low cost, simple fabrication, high sensitivity, selectivity, and stability [ 16 , 17 , 18 , 19 , 20 , 21 ]. Previously, electrochemical methods have been widely used for the detection of hazardous/toxic compounds or biomolecules [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the assembly of CMEs, it is vital to select a suitable modifier with enhanced electrocatalytic activity or excellent conductivity. The modification of GC, gold and platinum electrodes by nanoparticles/nanocomposites of transition metal oxides, their composites, and conducting polymers have emerged as a leading area of research during the last decade [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Mobin and the research team at IIT Indore developed a novel HQ sensor using the N-rGO/SrZrO 3 composite as an electrode material [ 1 ]. In 2019, Ahmad et al [ 21 ] also reported the fabrication of an HQ and catechol sensor using SnO 2 as the electrode material. In another work, Meskher et al fabricated NiO/rGO/f-MWCNTs on a platinum (Pt) electrode for the determination of HQ and catechol simultaneously [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors restrict rapid detection of serotonin with frequent testing, and it will be of great importance to discover or develop other alternative methods for rapid determination of serotonin [ 14 ]. Electrochemistry-based analytical or electrochemical methods have gained enormous attention because of their simple process, fast response/detection, ease of operation, and selectivity [ 15 , 16 , 17 , 18 , 19 ]. In addition, electrochemical techniques offer highly sensitive analysis with a cost-effective miniaturized platform [ 20 ].…”
Section: Introductionmentioning
confidence: 99%